"Arguments online, but in school we always act normal": The embeddedness of early adolescent negative peer interactions within the whole of their offline and online peer interactions. (February 2018) - Pabian, Sara; Erreygers, Sara; Vandebosch, Heidi; Van Royen, Kathleen; Dare, Julie; Costello, Leesa; Green, Lelia; Hawk, Dianne; Cross, Donna
Abstract: The goal of the present study was to investigate how negative peer interactions offline and online are associated with each other and with other daily interactions among early adolescents. To this aim, photo-elicitation interviewing was used to gather data among a sample of 34 early adolescents (13–14 years). A thematic analysis revealed that adolescents experience a wide range of different types of negative peer interactions offline and online. Most of the negative interactions recalled by the participants took place exclusively offline or online, and only a few were continued and/or managed in another environment. When participants were involved in online negative interactions they often acted as if nothing happened afterwards in the offline environment. On the other hand, offline negative interactions were often not continued online because the persons involved did not interact online. Further implications of the results for prevention and intervention, and for future research are discussed. Highlights: Adolescents experience daily a wide array of negative peer interactions. Adolescents react on these incidents mostly within the same context (on-/offline). Negative peer interactions are often not continued in another context. Adolescents act offline as if nothing happened after online negative interactions.